Comparison analysis of financial performance telecommunication service which has and has not applied PSAK 73 - Kloko, Deta Merilyn Elintra; Bayunitri, Bunga Indah (International Journal of Financial, Accounting, and Management, 2020)
Purpose: This research aimed to find out a comparative analysis of the financial performance of companies that has and has not applied the PSAK 73 or IFRS 16 of Lease. Research Methodology: The research used was quantitative descriptive method. The Financial performance analysis performed used a liability, solvency, activity, and profitability ratio. Results: From the research, it is known that by applying the PSAK 73 on lease in companies has an impact on the financial performance especially on the liability ratio and profitability ratio. Limitations: The narrowing of the study scope was only to industrial telecommunications due to the inability to collect all data from each type of business. In addition, the application of PSAK 73 in Indonesia was unforced to be implemented in companies in 2019 but in 2020. However, this regulation was possible to apply earlier in 2019 in only corporations meeting requirements. This was aimed at limiting the generalization of the study. Contribution: The result of this study is expected to be useful with regard to the application of PSAK 73 or IFRS 16 of Lease on financial performance in companies. Keywords: PSAK 73, IFRS 16, Lease, Financial performance